Electrophysiological characterization of medial preoptic neurons in lactating rats and its modulation by hypocretin-1. (November 2022) - Rivas, Mayda; Serantes, Diego; Pascovich, Claudia; Peña, Florencia; Ferreira, Annabel; Torterolo, Pablo; Benedetto, Luciana
Abstract: The medial preoptic area (mPOA) undergoes through neuroanatomical changes across the postpartum period, during which its neurons play a critical role in the regulation of maternal behavior. In addition, this area is also crucial for sleep-wake regulation. We have previously shown that hypocretins (HCRT) within the mPOA facilitate active maternal behaviors in postpartum rats, while the blockade of endogenous HCRT in this area promotes nursing and sleep. To explore the mechanisms behind these HCRT actions, we aimed to evaluate the effects of juxta-cellular HCRT-1 administration on mPOA neurons in urethane-anesthetized postpartum and virgin female rats. We recorded mPOA single units and the electroencephalogram (EEG) and applied HCRT-1 juxta-cellular by pressure pulses. Our main results show that the electrophysiological characteristics of the mPOA neurons and their relationship with the EEG of postpartum rats did not differ from virgin rats. Additionally, neurons that respond to HCRT-1 had a slower firing rate than those that did not. In addition, administration of HCRT increased the activity in one group of neurons while decreasing it in another, both in postpartum and virgin rats. This study suggests that the mechanisms by which HCRT modulate functions controlled by the mPOA involve different cell populations. Highlights: mPOA neurons of lactating and virgin rats have similar electrophysiological features. Lactating and virgin rats have a similar proportion of NREMure and REMure "ON" neurons. HCRT-1 produces opposite effects in different mPOA neurons. mPOA neurons that respond to HCRT-1 have a slower firing rate than those that do not.